Davis–Beirut reaction inspired nitroso Diels–Alder reaction. (13th April 2021) - Son, Jung-Ho; Cheung, Amy; Zhu, Jie S.; Haddadin, Makhluf J.; Kurth, Mark J.
Graphical abstract: Highlights: Davis–Beirut reaction inspired nitroso Diels–Alder protocol. Nitrophenyl starting material has the para position substituted with a 2°-amine or 2°-alcohol. Concomitant benzylic oxidation and nitro reduction delivers a nitrosophenyl intermediate. One-pot procedure delivers aryldihydro-1, 2-oxazines in moderate yields. Abstract: A Davis–Beirut reaction inspired nitroso Diels–Alder protocol is reported. The starting material for the procedure is a nitrophenyl moiety with the para position appropriately substituted with a 2°-amine (see 5 ) or 2°-alcohol (see 6 ). Deprotonation at the benzylic position followed by concomitant oxidation of the benzylic position and reduction of the nitro moiety delivers a nitrosophenyl intermediate, which subsequently undergoes a nitroso Diels–Alder reaction. This one-pot procedure delivers aryldihydro-1, 2-oxazines in moderate yields.